Analisis Model Arsitektur Enterprise Pada Sistem Informasi Dinas Pendidikan Kota Jambi - Masgo; Santoso (LPPM STIKOM Dinamika Bangsa, 2024)
Utilization of enterprise architecture in creating harmony between services and information technology to support the needs of the organization now and in the future. In order for an enterprise to successfully implement enterprise architecture, the task cannot be separated from the enterprise's success in determining how an organization is able to analyze and design the best enterprise architecture for it. We should use a complete and easy-to-use methodology in planning and designing enterprise architecture. The results of enterprise architecture modeling using the TOGAF ADM methodology provide a basis for overcoming problems that occur at the Jambi City Education Office, namely the lack of data integration and related system support, resulting in less productive performance effectiveness and efficiency. In this research, a case study was carried out for information system enterprise architecture planning using the TOGAF Architecture Development Method (ADM) method with the help of value chains and other modeling tools at the Jambi City Education Office. The stages of the TOGAF ADM methodology are translated into enterprise architecture modeling, namely vision architecture, business architecture, information systems architecture and technology architecture